Feeding tricarboxylic acid cycle intermediates improves lactate consumption and antibody production in Chinese hamster ovary cell cultures. (21st February 2020) - Zhang, Xiaolin; Jiang, Rubin; Lin, Henry; Xu, Sen
Abstract: Media components play an important role in modulating cell metabolism and improving product titer in mammalian cell cultures. To sustain cell productivity, highly active oxidative metabolism is desired. Here we explored the effect of tricarboxylic acid (TCA) cycle intermediates supplementation on lactate metabolism and productivity in Chinese hamster ovary fed‐batch cultures. Direct addition of 5 mM alpha‐ketoglutarate (α‐KG), malic acid, or succinic acid in the basal medium did not have any significant impact on culture performance. On the other hand, feeding α‐KG, malic acid, and succinic acid in the stationary phase, either as a single solution or as a mixture, significantly improved lactate consumption, reduced ammonium accumulation, and led to higher cell specific productivity and antibody titer ( 35% increase for the best condition). Delivering those intermediates as an acidic solution for pH control eliminated CO2 sparging and accumulation. Feeding TCA cycle intermediates was also demonstrated to be superior to feeding lactic acid or pyruvic acid in titer improvement. Taken together, feeding TCA cycle intermediates was effective in improving lactate consumption and increasing product titer, which is likely due to enhanced oxidative metabolism in an extended duration.